Crystalline easy-to-recover polyester heat-shrinkable film as well as preparation method and recovery application thereof

By preparing crystalline easily recycled polyester heat shrink film, the problem of degradation of performance after mixing with the physical recovery bottle sheet in the prior art is solved, and physical recycling and good performance are achieved with PET bottle sheets, which meets the requirements of environmental protection and circular economy.

CN119684764AActive Publication Date: 2025-03-25HENAN YINJINDA NEW MATERIALS CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510221361.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-25
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The existing non-crystalline copolyester heat shrink film is difficult to mix with the polyester bottle sheets recovered by physical method, resulting in a decrease in the heat shrinkage rate and palm fastness, and it is difficult to be recycled by physical method, which violates the requirements of environmental protection and circular economy.

Method used

By using the preparation method of crystalline easy-to-recover polyester heat shrink film, a film with good heat shrinkability and mechanical properties is prepared by mixing modified PET, PET bottle recycle material, modified copolyether, nucleating agent and additives, melt extrusion, quench molding, vertical and horizontal stretching and traction winding.

Benefits of technology

The physical recycling of polyester heat shrink film and PET bottles is achieved, and good heat shrinkability and mechanical properties are maintained, which meets the requirements of environmental protection and circular economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a crystalline easy-to-recover polyester heat-shrinkable film as well as a preparation method and recovery application thereof. The crystalline easy-to-recover polyester heat-shrinkable film is prepared from the following raw materials in percentage by mass: 55 to 63 percent of modified PET (Polyethylene Terephthalate), 20 to 63 percent of PET bottle flake recovered material, 5 to 10 percent of modified copolyether, 1 to 3 percent of nucleating agent and 0.1 to 0.5 percent of auxiliary agent. Wherein the modified copolyether is prepared by taking hydroxyl-terminated ethylene oxide-tetrahydrofuran copolyether and alkenyl acyl halide as raw materials through acylation reaction. Through proper formula design and a matched preparation process, the obtained polyester heat shrinkage film has higher melting point and heat shrinkage rate, and obtains proper crystallinity, so that the polyester heat shrinkage film can be better recycled together with a bottle flake recycled material with a large PET component proportion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyester shrinkage films, and in particular to a crystalline easily recyclable polyester heat shrinkage film and a preparation method and recycling application thereof. Background Art

[0002] Polyester heat shrinkable film is a widely used shrink sleeve label material. This technology usually uses non-crystalline copolyester resin to extrude a thick sheet through an extruder, and then obtains a film with unidirectional or bidirectional orientation of the polymer chain by one or both of longitudinal stretching and transverse stretching.

[0003] A typical feature of this heat shrinkable film is that the oriented film prepared by the above steps can shrink back to the state before stretching and orientation as much as possible when heated to between 50-100°C to obtain a larger shrinkage rate. Therefore, this technology usually requires the use of non-crystalline copolyester to ensure that no crystallization occurs during the stretching and orientation process of the thick sheet, because crystallization usually "freezes" the movement of the molecular chain, hindering its heat shrinkage ability at 50-100°C and reducing its heat shrinkage rate.

[0004] Another typical feature of heat shrinkable film is that the oriented film prepared by the above steps has good leveling properties when applied to the surface of the film using one or more conventional organic solvents in the industry, such as 1,4-dioxane, 1,3-dioxane, and tetrahydrofuran. It can dissolve or swell the surface layer of the film. When this dissolved or swollen surface layer is attached to another surface layer, it can be bonded together and maintain a certain bonding strength after the solvent evaporates. The industry uses this method to prepare the shrink film into a shrink sleeve. This necessary step is called "hand-to-hand", and the organic solvent used is called "hand-to-hand solvent". Generally speaking, non-crystalline polyester film is easily dissolved or swelled by hand-to-hand solvent, and the bonding strength of hand-to-hand can meet the application needs. However, if the crystallinity of the film increases, the hand-to-hand solvent will find it difficult to dissolve or swell the film, resulting in a decrease in hand-to-hand fastness, affecting subsequent use.

[0005] Although the above-mentioned non-crystalline copolyester heat shrinkable film has many advantages in application, its disadvantages and shortcomings are also obvious. First, this type of shrinkage film is difficult to mix with polyester bottle flakes recycled by physical method. The polyester bottle flakes recycled by physical method here refer to the recycled polyester bottle flakes obtained after consumers use the polyester bottle and then recycled by the recycling system, and then processed by physical methods such as crushing, cleaning, and drying. In particular, when the content of polyester bottle flakes recycled by physical method in the shrinkage film formula exceeds 25%, the heat shrinkage rate of the shrinkage film will decrease, and the fastness of the palm will decrease, thus affecting the use of the heat shrinkage film. This performance decline is essentially due to the fact that the polyester bottle flakes recycled by physical method are crystalline polymers. The mixing of such substances into the shrinkage film will increase the crystallinity of the film, thereby reducing both the shrinkage performance and the palm fastness.

[0006] Second, this type of shrink film is difficult to recycle using physical methods. Because the non-crystalline film has no crystals and a low softening point, when it undergoes the aforementioned physical recycling process, it gradually softens, causing the recycled bottle flakes to stick together and agglomerate, resulting in the entire recycling system not being able to operate normally. Of course, if a large amount of crystalline recycled bottle flakes are mixed, it is beneficial to improve the adhesion and agglomeration, but as mentioned in the first disadvantage above, mixing crystalline polymers will cause the shrinkage performance and hand-jointing performance of the shrink film to decrease, so it is difficult to achieve a balance in practical applications.

[0007] As countries around the world pursue environmental protection and circular economy, more and more food and beverage brands are paying more and more attention to packaging materials containing recycled materials and being recyclable. Many countries have also specified roadmaps requiring packaging materials to contain 30% or more recycled materials. In the polyester field, the so-called "recycled materials" usually refer to recycled bottles supported by a complete recycling system, and these recycled materials are all crystalline polyesters. For a long time, the widely used non-crystalline copolyester heat shrink film has been considered difficult to add 30% of physical recycled materials and can no longer be physically recycled. This is inconsistent with the current circular environmental protection model advocated by the plastic packaging industry of "using more recycled materials and recyclable packaging".

[0008] In order to solve the problem that non-crystalline membranes cannot use recycled materials in large quantities and cannot be recycled, the industry usually uses chemical methods for recycling and reuse. The chemical method refers to the method of depolymerizing used polyester waste under high temperature conditions by chemical methods to obtain small molecular monomers or oligomers, and then purifying these monomers, and using these purified monomers to repolymerize into polyester or industrial polyester under high temperature conditions. Although this chemical recycling method has achieved a certain degree of recycling cycle, it adds two high-energy-consuming depolymerization and repolymerization steps, which is obviously contrary to the concept of low-carbon and environmental protection. Summary of the invention

[0009] In view of this, the object of the present invention is to provide a crystalline and easily recyclable polyester heat shrinkable film and a preparation method and application thereof. The polyester heat shrinkable film provided by the present invention can be physically recycled together with polyester bottle flakes and has good heat shrinkage and mechanical properties.

[0010] In order to achieve the above invention objectives, the present invention provides the following technical solutions: A crystalline and easily recyclable polyester heat shrinkable film comprises the following raw materials: in terms of mass percentage, 55-63% of modified PET, 20-50% of recycled PET bottle flakes, 5-10% of modified copolyether, 1-3% of a nucleating agent and 0.1-0.5% of an auxiliary agent.

[0011] In some embodiments of the present invention, the modified PET is prepared by esterification and polymerization of a dibasic acid and a diol, wherein, based on 100 mol% of the total dibasic acid components, the dibasic acid includes at least 0-3 mol% of isophthalic acid and 97-100 mol% of terephthalic acid; based on 100 mol% of the total diol components, the diol includes at least 7-35 mol% of neopentyl glycol, 0-12 mol% of cyclohexanedimethanol and the remaining percentage of ethylene glycol.

[0012] In some embodiments of the present invention, the modified PET has an intrinsic viscosity IV of 0.74-0.82 dl / g; a terminal carboxyl content of <35 mol / t; and among its L*A*B values, the B value is ≤2.2, and the L value is >56.

[0013] In some embodiments of the present invention, the modified copolyether is prepared by reacting a terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether with an olefinic acid halide, and the preparation process comprises the following steps: S1: Add terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether into a reaction vessel, heat and reduce pressure to remove water, and then cool to room temperature; S2: Add an organic solvent and an amine catalyst to the system obtained in S1, cool it with an ice bath, and start to dropwise add the organic solution of the olefinic acid halide. After the dropwise addition is complete, continue the reaction for 24 hours; S3: The reaction liquid obtained in S2 is washed with water until it becomes neutral, separated, and the oil phase is decompressed to evaporate the solvent to obtain the modified ethylene oxide-tetrahydrofuran copolyether.

[0014] Furthermore, in S1, the preparation process of the terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether comprises the following steps: adding boron trifluoride ether complex, ethylene glycol and toluene to a three-necked flask, stirring evenly at -25-0°C, and then adding a mixed monomer of ethylene oxide and tetrahydrofuran to react; after reacting for 5-7 hours, adding distilled water, continuing to stir for 10-15 minutes, terminating the reaction, washing the product to neutrality, then distilling off toluene, and vacuum drying at 70-80°C to obtain a terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether with a relative molecular mass of 3300-3900.

[0015] Furthermore, the molar ratio of ethylene oxide to tetrahydrofuran is 5-8:2-5.

[0016] Furthermore, the heating, depressurizing and water removal temperature in S1 is 90-100°C.

[0017] Furthermore, the temperature of the ice bath cooling in S2 is 0-2°C.

[0018] Furthermore, the olefinic acid halide in S2 is at least one of propylene acid chloride, crotonyl chloride, 3-methyl crotonyl chloride, 3-cis-methyl-isobutylene acid chloride, (E)-pent-2-enoyl chloride, (E)-hex-2-enoyl chloride, and sorbic acid chloride.

[0019] Furthermore, in the organic solution of alkenyl acyl halide in S2, the mass fraction of alkenyl acyl halide is 2.0-2.2 g / ml.

[0020] Furthermore, the mass ratio of the terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether, the amine catalyst, and the olefinic acid halide described in S1 and S2, respectively, is 680-700:65-70:40-45.

[0021] Furthermore, the amine catalyst is triethylamine, NN-dimethylcyclohexylamine, N,N-dimethylbenzylamine, N,N-dimethylpyridine, triethylenediamine, trimethylbenzylamine, dimethylethanolamine, and the like.

[0022] In some embodiments of the present invention, the nucleating agent is any one of the sodium salt or zinc salt of ethylene-methacrylic acid polymer.

[0023] In some embodiments of the present invention, the auxiliary agent includes a lubricant and / or an anti-sticking agent, the lubricant is oleamide and / or erucamide, and the anti-sticking agent is silicon powder, silicon dioxide or talc.

[0024] The present invention provides a method for preparing the above-mentioned crystalline easily recyclable polyester heat shrinkable film, comprising the following steps: mixing modified PET, PET bottle flakes recycled material, modified ethylene oxide-tetrahydrofuran copolyether, a nucleating agent and an auxiliary agent, performing melt extrusion, and forming into a cast sheet after rapid cooling; and sequentially performing longitudinal stretching, transverse stretching and traction and winding of the cast sheet to obtain the recyclable polyester heat shrinkable film.

[0025] Furthermore, the melt extrusion is performed by a twin-screw extruder, and the temperature of the melt extrusion is preferably 240-270° C. In the present invention, the rapid cooling is preferably to attach the extrudate obtained by the melt extrusion to a chilled roll for rapid cooling.

[0026] Furthermore, the longitudinal stretching includes sequentially performing a first preheating longitudinal stretching and a first cooling and shaping on the cast sheet.

[0027] Furthermore, the first preheating temperature is 60-80°C, the longitudinal stretching temperature is 100-120°C, the stretching ratio is 1.2-2 times, and the first cooling and setting temperature is 40-60°C.

[0028] Furthermore, the transverse stretching includes sequentially performing a second preheating transverse stretching and a second cooling and shaping on the longitudinally stretched film.

[0029] Furthermore, the second preheating temperature is 105-110°C, the transverse stretching temperature is 95-100°C, the stretching ratio is 2-3 times, and the second cooling and setting temperature is 50-60°C.

[0030] The present invention also provides the use of the polyester heat shrinkable film in the field of PET bottle label materials after ink cleaning.

[0031] In some embodiments of the present invention, before application, the ink is cleaned with 1-5% sodium hydroxide solution or a surfactant, and the de-inking time is 25-30 seconds.

[0032] Beneficial effects: Compared with the prior art, the PET bottle flakes recycled material in the present invention has a higher proportion, which can improve the crystallinity of the film material to a certain extent and increase the tensile strength of the film; at the same time, modified copolyether is added: on the one hand, the molecular weight of the material is increased, and the crystallization temperature of the material is further increased; on the other hand, the olefin groups at both ends of the modified copolyether can play a similar "adhesion" role to improve the fusion of the crystalline bottle flakes recycled material and the modified PET; on the other hand, the modified copolyether, as an amorphous material, makes the heat shrinkable film have a certain amorphous structure, and its glass transition temperature is very low, thereby ensuring that the heat shrinkable film has a high heat shrinkage rate. Finally, the heat shrinkable film has good recyclability and a high heat shrinkage rate. In addition, the present invention limits the raw material composition and physical parameters of the modified PET, and uses it together with the modified copolyether to prepare the heat shrinkable polyester film, so that the heat shrinkable polyester film can quickly wash out the ink under the action of low concentration of alkali solution or surfactant, and realize efficient recycling application. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known to those skilled in the art. Specifically, the nucleating agent is surlyn 8940 (DuPont, USA).

[0035] The following is an exemplary description of the preparation process of the modified ethylene oxide-tetrahydrofuran copolyether used in the examples: Modified copolyether-1 S1: Add 6.8 parts of hydroxy-terminated ethylene oxide-tetrahydrofuran copolyether (relative molecular weight 3350) into a three-necked flask equipped with a mechanical stirrer and a thermometer, heat to 90°C and remove water under reduced pressure for 1.5 hours, then cool to room temperature; S2: Add 60 parts of dichloromethane and 0.65 parts of triethylamine to the system obtained in S1, cool to 0°C with an ice bath, and start to drop 20 parts of a dichloromethane solution of 2.0 g / ml acryloyl chloride. After the dropwise addition is completed within 6 hours, continue the reaction for 24 hours; S3: The reaction liquid obtained in S2 is washed with water until it becomes neutral, separated, and the oil phase is decompressed to evaporate the solvent to obtain the modified ethylene oxide-tetrahydrofuran copolyether-1.

[0036] Wherein, the preparation process of the hydroxy-terminated ethylene oxide-tetrahydrofuran copolyether described in S1 is as follows: 1.2 mol of boron trifluoride ether complex, 1.2 mol of ethylene glycol and 1000 ml of toluene were added to a three-necked flask, and after stirring evenly at -25°C, 2 mol of a mixed monomer of ethylene oxide and tetrahydrofuran in a molar ratio of 5:5 was added to react; after reacting for 5 hours, distilled water was added, and stirring was continued for 10 minutes to terminate the reaction, and the product was washed to neutrality, and then the toluene was distilled off and vacuum dried at 70°C to obtain the terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether.

[0037] Modified copolyether-2 S1: Add 6.9 parts of hydroxy-terminated ethylene oxide-tetrahydrofuran copolyether (relative molecular weight 3510) into a three-necked flask equipped with a mechanical stirrer and a thermometer, heat to 95°C and remove water under reduced pressure for 1 hour, then cool to room temperature; S2: Add 60 parts of dichloromethane and 0.67 parts of NN-dimethylcyclohexylamine to the system obtained in S1, cool to 1°C with an ice bath, and start to drop 20 parts of a dichloromethane solution of crotonyl chloride with a mass fraction of 2.1 g / ml. After the dropwise addition is completed within 6 hours, continue the reaction for 24 hours; S3: The reaction liquid obtained in S2 is washed with water until it becomes neutral, separated, and the oil phase is decompressed to evaporate the solvent to obtain the modified ethylene oxide-tetrahydrofuran copolyether-2.

[0038] Wherein, the preparation process of the hydroxy-terminated ethylene oxide-tetrahydrofuran copolyether described in S1 is as follows: 1.3 mol of boron trifluoride ether complex, 1.3 mol of ethylene glycol and 1000 ml of toluene were added to a three-necked flask, and after stirring evenly at -15°C, 2 mol of a mixed monomer of ethylene oxide and tetrahydrofuran in a molar ratio of 7:3 was added to react; after reacting for 6 hours, distilled water was added, and stirring was continued for 12 minutes to terminate the reaction, and the product was washed to neutrality, and then the toluene was distilled off and vacuum dried at 75°C to obtain the terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether.

[0039] Modified copolyether-3 S1: Add 7.0 parts of hydroxy-terminated ethylene oxide-tetrahydrofuran copolyether (relative molecular weight 3760) into a three-necked flask equipped with a mechanical stirrer and a thermometer, heat to 100°C and remove water under reduced pressure for 0.5h, then cool to room temperature; S2: Add 60 parts of ethylene dichloride and 0.70 parts of triethylene diamine to the system obtained in S1, cool to 2°C with an ice bath, and start to drop 20 parts of a 2.2 g / ml solution of (E)-pent-2-enoyl chloride in ethylene dichloride. After the dropwise addition is completed within 6 hours, continue the reaction for 24 hours; S3: The reaction liquid obtained in S2 is washed with water until it becomes neutral, separated, and the oil phase is decompressed to evaporate the solvent to obtain the modified ethylene oxide-tetrahydrofuran copolyether-3.

[0040] Wherein, the preparation process of the hydroxy-terminated ethylene oxide-tetrahydrofuran copolyether described in S1 is as follows: 1.4 mol of boron trifluoride ether complex, 1.4 mol of ethylene glycol and 1000 ml of toluene were added to a three-necked flask, and after stirring evenly at 0°C, 2 mol of a mixed monomer of ethylene oxide and tetrahydrofuran in a molar ratio of 8:2 was added to react; after reacting for 7 hours, distilled water was added, and stirring was continued for 15 minutes to terminate the reaction, and the product was washed to neutrality, and then the toluene was distilled off and vacuum dried at 80°C to obtain the terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether. Example 1

[0041] Preparation of crystalline and easily recyclable polyester heat shrinkable film: 55% of modified PET (intrinsic viscosity IV of 0.74 dl / g, terminal carboxyl content of 20 mol / t, B value = 2.0, L value = 60), 48.9% of PET bottle flakes recycled material, 5% of modified copolyether-1, 1% of nucleating agent and 0.2% of auxiliary agent (0.1% erucic acid amide and 0.1% of silicon powder) are added into a high-speed mixer to obtain a mixture, and the mixture is sent into a twin-screw extruder for melt extrusion (temperature 240° C.), and the extrudate is attached to a chilled roller (temperature 25-35° C.) and rapidly cooled to form a casting sheet; After preheating the cast sheet at 60°C for 10s, the sheet was stretched at 100°C in the longitudinal direction with a stretching ratio of 1.2 times, and then cooled at 60°C for finalization; After longitudinal stretching, the film was preheated at 105°C for 10s, then stretched in the transverse direction at 95°C with a stretching ratio of 2, and then cooled at 60°C for finalization; then the film was subjected to online thickness measurement and finally pulled and rolled. Example 2

[0042] Preparation of crystalline and easily recyclable polyester heat shrinkable film: 59% of modified PET (intrinsic viscosity IV of 0.78 dl / g, terminal carboxyl content of 31 mol / t, B value = 2.1, L value = 64), 41.6% of PET bottle flakes recycled material, 7% of modified copolyether-2, 2% of nucleating agent and 0.4% of auxiliary agent (0.2% erucic acid amide and 0.2% of silicon powder) are added into a high-speed mixer to obtain a mixture, and the mixture is sent into a twin-screw extruder for melt extrusion (temperature 250° C.), and the extrudate is attached to a chilled roller (temperature 25-35° C.) and rapidly cooled to form a casting sheet; After preheating the cast sheet at 70°C for 10s, the sheet was stretched at 110°C in the longitudinal direction with a stretching ratio of 1.5 times, and then cooled at 50°C for finalization; After longitudinal stretching, the film was preheated at 105°C for 10s, then stretched in the transverse direction at 95°C with a stretching ratio of 2.5 times, and then cooled at 55°C for finalization; then the film was subjected to online thickness measurement and finally pulled and rolled. Example 3

[0043] Preparation of crystalline and easily recyclable polyester heat shrinkable film: 63% of modified PET (intrinsic viscosity IV of 0.80 dl / g, terminal carboxyl content of 33 mol / t, B value = 1.9, L value = 67), 22.5% of PET bottle flakes recycled material, 10% of modified copolyether-3, 5% of nucleating agent and 0.5% of auxiliary agent (0.2% erucic acid amide and 0.3% of silicon powder) are added into a high-speed mixer to obtain a mixture, and the mixture is sent into a twin-screw extruder for melt extrusion (temperature 270° C.), and the extrudate is attached to a chilled roller (temperature 25-35° C.) and rapidly cooled to form a casting sheet; After preheating the cast sheet at 80°C for 10s, the sheet was stretched at 120°C in the longitudinal direction with a stretching ratio of 2 times, and then cooled at 60°C for finalization; After longitudinal stretching, the film was preheated at 110°C for 10s, then stretched at 100°C in the transverse direction with a stretching ratio of 3 times, and then cooled at 50°C for finalization; then the film was measured online for thickness, and finally pulled and rolled. Comparative Example 1

[0044] Same as Example 3, except that the modified copolyether-3 used is not modified with (E)-pent-2-enoyl chloride. Comparative Example 2

[0045] Same as Example 3, except that modified copolyether-3 is not used. Performance Testing

[0046] Tensile strength and elongation at break: tested according to ASTM D882; Thermal shrinkage: tested according to ASTM D1204; Lump test: refer to the relevant methods of APR PET CG-02Criticl Guidance: dry the shrunken broken film pieces in a 160℃ oven for 0.5h, mix the dried broken film pieces with bottle pieces in a ratio of 1:3, bake them in a 210℃ oven for 90min and take them out. If the mass of the material sticky with the bottle pieces does not exceed 1% of the total mass of the mixture, it is considered to have passed, otherwise it is considered to have failed.

[0047] The test results are shown in Table 1.

[0048] Table 1 Test results of polyester heat shrinkable films obtained in Examples 1-3 and Comparative Examples 1-2

[0049] It can be seen from the test results in Table 1 that the polyester heat shrinkable film obtained by the present invention has a high melting point and a suitable crystallinity through a suitable formula design and a matching preparation process, so that it can be recycled together with PET bottles. It also has good heat shrinkage and mechanical properties. However, the comparative example that does not use the specified modified copolyether fails to pass the agglomeration test and does not have the recyclability to be easily recycled together with PET bottle flakes.

Claims

1. A crystalline and easily recyclable polyester heat shrinkable film, characterized in that: The preparation raw materials include: in terms of mass percentage, 55-63% of modified PET, 20-50% of recycled PET bottle flakes, 5-10% of modified copolyether, 1-3% of nucleating agent and 0.1-0.5% of auxiliary agent.

2. The crystalline and easily recyclable polyester heat shrinkable film according to claim 1, characterized in that: The modified PET is prepared by esterification and polymerization of a dibasic acid and a diol, wherein, based on 100 mol % of the total dibasic acid components, the dibasic acid at least includes 0-3 mol % of isophthalic acid and 97-100 mol % of terephthalic acid; based on 100 mol % of the total diol components, the diol at least includes 7-35 mol % of neopentyl glycol, 0-12 mol % of cyclohexanedimethanol and the remaining percentage of ethylene glycol.

3. The crystalline and easily recyclable polyester heat shrinkable film according to claim 2, characterized in that: The modified PET has an intrinsic viscosity IV of 0.74-0.82 dl / g; a terminal carboxyl content of <35 mol / t; and in its L*A*B value, the B value is ≤2.2, and the L value is >56.

4. The crystalline and easily recyclable polyester heat shrinkable film according to claim 1, characterized in that: The modified copolyether is prepared by reacting terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether with alkenyl acyl halide, and the preparation process comprises the following steps: S1: Add terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether into a reaction vessel, heat and reduce pressure to remove water, and then cool to room temperature; S2: Add an organic solvent and an amine catalyst to the system obtained in S1, cool it with an ice bath, and start to dropwise add the organic solution of the olefinic acid halide. After the dropwise addition is complete, continue the reaction for 24 hours; S3: The reaction liquid obtained in S2 is washed with water until it becomes neutral, separated, and the oil phase is decompressed to evaporate the solvent to obtain the modified ethylene oxide-tetrahydrofuran copolyether.

5. The crystalline and easily recyclable polyester heat shrinkable film according to claim 4, characterized in that: In S1, the preparation process of terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether comprises the following steps: adding boron trifluoride ether complex, ethylene glycol and toluene into a three-necked flask, stirring evenly at -25-0°C, and then adding a mixed monomer of ethylene oxide and tetrahydrofuran to react; after reacting for 5-7 hours, adding distilled water, continuing to stir for 10-15 minutes, terminating the reaction, washing the product to neutrality, then distilling off toluene, and vacuum drying at 70-80°C to obtain terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether with a relative molecular mass of 3300-3900.

6. The crystalline and easily recyclable polyester heat shrinkable film according to claim 5, characterized in that: The molar ratio of ethylene oxide to tetrahydrofuran is 5-8:2-5.

7. The crystalline and easily recyclable polyester heat shrinkable film according to claim 4, characterized in that: The heating and depressurizing water removal temperature in S1 is 90-100°C; the ice bath cooling temperature in S2 is 0-2°C; the olefinic acid halide in S2 is at least one of propylene acid chloride, crotonyl chloride, 3-methyl crotonyl chloride, 3-cis-methyl-isobutylene acid chloride, (E)-pent-2-enoyl chloride, (E)-hex-2-enoyl chloride, and sorbic acid chloride; in the organic solution of the olefinic acid halide, the mass fraction of the olefinic acid halide is 2.0-2.2 g / ml.

8. The crystalline and easily recyclable polyester heat shrinkable film according to claim 4, characterized in that: The mass ratios of the terminal hydroxyl ethylene oxide-tetrahydrofuran copolyether, the amine catalyst and the olefinic acid halide in S1 and S2 are 680-700:65-70:43-45 respectively.

9. The method for preparing the crystalline easily recyclable polyester heat shrinkable film according to claims 1-8, characterized in that: The method comprises the following steps: mixing modified PET, recycled PET bottle flakes, modified copolyether, a nucleating agent and an auxiliary agent, performing melt extrusion, and forming into a cast sheet after rapid cooling; and sequentially performing longitudinal stretching, transverse stretching and traction and winding on the cast sheet to obtain the recyclable polyester heat shrinkable film.

10. The crystalline and easily recyclable polyester heat shrinkable film according to any one of claims 1 to 8 is recycled and applied in the field of PET bottle label materials after ink cleaning.

Citation Information

Patent Citations

  • Polyester polyols from recycled polymers and waste streams

    CN107087412A

  • Electromagnetic radiation-proof transparent material for touch screen and preparation method of electromagnetic radiation-proof transparent material

    CN107556741A

  • Polyalkenyl-terminated copolyether bonding agent and synthesis method thereof

    CN107739588A

  • Synthesis process of A(B)n type copolymer from hydroxyl or amine compound

    CN1166503A

  • Crystalline easy-to-recover polyester heat-shrinkable film and preparation method thereof

    CN117021725A